Resource Dependence Theory: A Review - Hillman, Amy J.; Withers, Michael C.; Collins, Brian J. (Journal of Management, 2009)
Thirty years have passed since Pfeffer and Salancik’s seminal work on resource dependence theory (RDT). During this time RDT has been applied broadly across the research domain to explain how organizations reduce environmental interdependence and uncertainty. In this review, the authors assess the conceptual development, empirical research, and application of RDT. They structure their review around the five options that Pfeffer and Salancik propose firms can enact to minimize environmental dependences: (a) mergers/vertical integration, (b) joint ventures and other interorganizational relationships, (c) boards of directors, (d) political action, and (e) executive succession.The authors summarize past work, synthesize contemporary thought, and propose future research directions.